The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.neuroscience.2008.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Timing of sound-evoked potentials and spike responses in the inferior colliculus of awake bats

Abstract: Neurons in the inferior colliculus (IC), one of the major integrative centers of the auditory system, process acoustic information converging from almost all nuclei of the auditory brain stem. During this integration, excitatory and inhibitory inputs arrive to auditory neurons at different time delays. Result of this integration determines timing of IC neuron firing. In the mammalian IC, the range of the first spike latencies is very large (5-50 ms). At present, a contribution of excitatory and inhibitory inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 53 publications
(93 reference statements)
2
21
0
Order By: Relevance
“…It has also been demonstrated that neurons exhibiting forward suppression that persists for hundreds of milliseconds do not show inhibitory conductances for longer than 50–100 ms. In our present and previous intracellular studies (Voytenko and Galazyuk 2007, 2008), we also rarely observed membrane hyperpolarizations in the IC lasting longer than 50 ms, even though suppression can last for hundreds of milliseconds. In an attempt to identify a possible cellular mechanism underlying this long-lasting suppression, we tested whether input resistance in IC neurons was altered during the suppression.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…It has also been demonstrated that neurons exhibiting forward suppression that persists for hundreds of milliseconds do not show inhibitory conductances for longer than 50–100 ms. In our present and previous intracellular studies (Voytenko and Galazyuk 2007, 2008), we also rarely observed membrane hyperpolarizations in the IC lasting longer than 50 ms, even though suppression can last for hundreds of milliseconds. In an attempt to identify a possible cellular mechanism underlying this long-lasting suppression, we tested whether input resistance in IC neurons was altered during the suppression.…”
Section: Discussionsupporting
confidence: 77%
“…9A, C, E). When the sound level was increased to 80 dB SPL, this neuron showed typical response patterns for IC neurons: IPSP-EPSP-spike-IPSP (Voytenko and Galazyuk, 2007, 2008; Peterson et al, 2008) followed by a suppression of spontaneous firing that lasted about 100 ms (Fig. 9B).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…30 dB nHL). This fi nding can be explained, at least partially, by the fact that high stimulus intensities produce better neural-fi ring effi ciency and less temporal jitter in single neuron recordings in the auditory nerve (Miller et al, 2006;Imennov & Rubinstein, 2009), and brainstem nuclei (Keller & Takahashi, 2000;Voytenko & Galazyuk, 2008). Briefl y, fi ring effi ciency can be computed as a ratio of the number of neuronal spikes elicited and the number of times the stimulus is presented.…”
Section: Exponential Modeling Of the Ffr Trends Of Pitch-encoding In mentioning
confidence: 99%
“…It has been shown previously that the first-spike latency contains important information in auditory, visual, olfactory, and somatosensory modalities (Furukawa & Middlebrooks, 2002;Kalluri & Delgutte, 2003;Panzeri, Petersen, Schultz, Lebedev, & Diamond, 2001;Reich, Mechler, & Victor, 2001;Rospars, Lansky, Duchamp, & DuchapViret, 2003). Namely, experimental results have demonstrated that spike timing carries additional information to the spike rate (Wiener & Richmond, 2003;Voytenko & Galazyuk, 2008;Perrinet, Samuelides, & Thorpe, 2004;. Due to these reasons, determination of the response latencies of one or more neurons was studied under different situations.…”
Section: Introductionmentioning
confidence: 99%